Efficient Signcryption with Verifiable DesigncryptionFor Sharing Personal Health Record - V, Chethan; Kumar, Vijay N; Deep, Karan SV; Pallavi, Pallavi; BN, Jagadeesh (International Journal of Computer Sciences and Engineering, 2025)
PHR is a patient-centric approach of health information exchange, that allows to store, access and to share the personal health information. To share confidential resources at the optimal cost, the PHR service providers are willing to keep the health information in the cloud. Some of the private agencies can expose the health information to some unauthorized persons because patient will not be having the physical control of the PHR. So To Overcome this problem, CipherText-Policy Attribute Based Signcryption is employed for sharing the PHR. It provides a access Control, confidentiality, authenticity of the Information. But it brings a high computational overhead and low efficiency in designcryption process. so some of the major computation are given to the Ciphertext Transformed Server that leaves only a small burden to the PHR User.The system is also capable of computing some unexpected Computations. Futhermore theoretical analysis and desired security properties includes confidentiality, unforgetability and verifiability has been proved in random oracle model.